Upaya Meningkatkan Hasil Belajar Matematika Melalui Pendekatan CBSA Pada Peserta Didik Kelas V.A SDN 18 Lembah Melintang - Arjuni S.Pd (STKIP Pesisir Selatan, 2016)
Abstract The problems to be examined in this study is: Does the use of CBSA approach can improve learning outcomes V.A grade math students of SDN 18 Valley Crossing? The purpose of this action research was to determine the learning outcome approach mathematics through the use of CBSA learners V.A grade SDN 18 Valley Crossing This study uses classroom action research as much as two rounds. Each round consists of four phases: planning, implementation, observation and reflection. Goal of this research is V.A grade students of SDN 18 Valley Crossing. The data obtained are kualitatif.Dari quantitative data and analysis results can be seen which approach CBSA have a positive impact in improving the learning outcomes of students characterized by increased completeness of learners in each cycle, ie pre-cycle (52.63%), the first cycle (73.68 %), the second cycle (86.84%). Keywords: Mathematics, CBSA approach, learning outcomes